2016
DOI: 10.1080/1553118x.2016.1150281
|View full text |Cite
|
Sign up to set email alerts
|

In the Wake of New Media: Connecting the Who with the How of Strategizing Communication

Abstract: In this article we argue that although there has been an intensified exploration of how organizations strategize within the field of strategic communication, there seems to be a key component missing, namely questioning who these organizations are and become in the process of strategizing. Strategic communication implicitly, perhaps even unintentionally, continues to rely on a classical understanding of organizations as "social units (or human groupings) deliberately constructed and reconstructed to seek speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
0
23
0
3
Order By: Relevance
“…Strategy is thus a communicative practice that is conducted at different levels in an organization as the organization is continuously created and reproduced. Increasingly, researchers in strategic communication adopt a more complex understanding of strategy by using the strategy as practice approach (Aten & Thomas, 2016;Frandsen & Johansen, 2015;Gulbrandsen & Just, 2016). This perspective of strategy is closely related to the CCO perspective, because both embrace the performative and sensemaking aspect of communication.…”
Section: Lack Of Meta-theoretical Reflectionsmentioning
confidence: 99%
“…Strategy is thus a communicative practice that is conducted at different levels in an organization as the organization is continuously created and reproduced. Increasingly, researchers in strategic communication adopt a more complex understanding of strategy by using the strategy as practice approach (Aten & Thomas, 2016;Frandsen & Johansen, 2015;Gulbrandsen & Just, 2016). This perspective of strategy is closely related to the CCO perspective, because both embrace the performative and sensemaking aspect of communication.…”
Section: Lack Of Meta-theoretical Reflectionsmentioning
confidence: 99%
“…The construct includes three indicators referring to internal communication, and two indicators that refer to both internal and external communication. As such, the construct disregards the rather artificial division between internal and external communication (Gulbrandsen & Just, 2016b), and presents a suggestion for how to approach employees responsibilities as regards communication which, due to the increasing demand for collaboration, interaction and participation in modern organizations, have become increasingly important to address (Gulbrandsen & Just, 2016a). While all other factors have high alphas, the reliability test on the items measuring employee communication responsibility revealed that this set of items has an alpha below 0.7, which is often considered as cut-off point (Nunnally, 1978).…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
“…As the communication responsibility of employees is receiving increasing attention from researchers arguing that new media changes the prerequisites for organizations and increases the demand for organizational members to take responsibility for communication (Gulbrandsen & Just, 2016a), and that all organizational members need to take responsibility for effective communication (Heide & Simonsson, 2011;Mazzei, 2014;Zerfass & Franke, 2013), this study is a timely contribution providing knowledge about factors that influence employees predisposition towards taking communication responsibility. It adds to the growing body of research interested in the communication of employees and complements and confirms previous research arguing for the importance of considering internal communication enablement strategies for turning employees into strategic communicators (Mazzei, 2014), studying the communication behavior of employees offline and online (Kang & Sung, 2017;Kim & Rhee, 2011;Madsen & Verhoeven, 2016), and arguing for the importance of increasing employees awareness about communication and to educate and counsel them to improve their communication skills (Heide & Simonsson, 2011;Zerfass & Franke, 2013).…”
Section: Structural Equation Model Analysismentioning
confidence: 99%
“…With inspiration from Gulbrandsen and Just (2016), we offer suggestions for relevant analytical questions and methods in Table 3. The combination of a relational view of agency, an interest in opening up technology and an agnostic, symmetrical methodological approach establishes a foundation for studying strategy and new media in a way that can begin to compensate for the gaps in the literature identified in this review.…”
Section: A Way Forwardmentioning
confidence: 99%
“…This new route can shape a future research agenda on strategy and new media. With inspiration from Gulbrandsen and Just (2016), we offer suggestions for relevant analytical questions and methods in Table 3.…”
Section: A Way Forwardmentioning
confidence: 99%